Megerian Carpet ընկերութեան քայլերը' հայկական գորգի վերածնունդին ուղղութեամբ - Սայադեան, Յասմիկ (տպ. Atlas)
The paper outlines the outstanding work the Megerian Carpet company has initiated in the Republic of Armenia Originally from Chomaklu, the Megerians founded their company in 1917 in New York as an antique rug selling and repairing company. After the proclamation of independence of Armenia, the company established a branch in Armenia, with the intention of promoting the Armenian rug ion the world market. In 2002 the company bought Haygorg, the old Soviet Armenian rug factory in Yerevan, and made it its Armenia headquarters. This step gave the company further impetus to restore old Armenian rug-weaving traditions like the usage of Armenian knots, the dying of the wool using natural materials including plants and other natural dyes, fixing the color of the dye on the wool, and matching the density of the knots to the number of knots in a square centimeter in ancient Armenian rugs. The company set up branches in different regions and towns of the Republic. These were to be further enlarged had there not been the Covid 19 setback and international market crises.
Keywords: Գորգագործութիւն